Implementation of Health Education Using Booklet Media on the Impact of Free Association Toward Adolescents' Knowledge Level - Hasnawati, Saptiah; Dwi Oktisa, Sherly (Asy-Syifa : Journal of Science and Technology Nursing, 2025)
Purpose: The purpose of this study was to determine the application of health education with booklet media about the impact of promiscuity on the level of knowledge of adolescents. Methods: This research method uses a descriptive with a case study approach. This study was conducted with 30 respondents on adolescents at SMP Fikri, Koja, North Jakarta. Result: The results showed that 30 respondents experienced an increase in knowledge, with the results of the value before health education was carried out, namely with a level of knowledge less than 1 respondent (3%), with a sufficient level of knowledge as many as 16 respondents (54%), and with a good level of knowledge as many as 13 respondents (43%). Then after health education was carried out about the impact of promiscuity with booklet media, namely with the category of good knowledge level as many as 28 respondents (93%) and with sufficient knowledge level as many as 2 respondents (7%). Conclusion: From the results of the research obtained, it can be concluded that the application of health education with booklet media about the impact of promiscuity has a significant influence on the level of knowledge of adolescents.